Modelling combined virotherapy and immunotherapy: strengthening the antitumour immune response mediated by IL-12 and GM-CSF expression. (30th June 2018) - Jenner, Adrianne L.; Yun, Chae-Ok; Yoon, Arum; Coster, Adelle C. F.; Kim, Peter S.
Abstract : Combined virotherapy and immunotherapy has been emerging as a promising and effective cancer treatment for some time. Intratumoural injections of an oncolytic virus instigate an immune reaction in the host, resulting in an influx of immune cells to the tumour site. Through combining an oncolytic viral vector with immunostimulatory cytokines an additional antitumour immune response can be initiated, whereby immune cells induce apoptosis in both uninfected and virus infected tumour cells. We develop a mathematical model to reproduce the experimental results for tumour growth under treatment with an oncolytic adenovirus co-expressing the immunostimulatory cytokines interleukin 12 (IL-12) and granulocyte-monocyte colony stimulating factor (GM-CSF). By exploring heterogeneity in the immune cell stimulation by the treatment, we find a subset of the parameter space for the immune cell induced apoptosis rate, in which the treatment will be less effective in a short time period. Therefore, we believe the bivariate nature of treatment outcome, whereby tumours are either completely eradicated or grow unbounded, can be explained by heterogeneity in this immune characteristic. Furthermore, the model highlights the apparent presence of negative feedback in the helper T cell and APC stimulation dynamics, when IL-12 and GM-CSF are co-expressed as opposed to individually expressed by the viral vector.